Disproportionation of ethylbenzene in the presence of C-8 aromatics - Sharnappa, N.; Pai, S.; Bokade, Vijay V. (Journal of Natural Gas Chemistry, 2009)
The selective synthesis of p-diethylbenzene (p-DEB) by disproportionation of ethylbenzene (EB) in the presence of aromatics like m- and p-xylene isomers has been studied over a pore size regulated HZSM-5 catalyst. The industrial feed having different compositions of ethylbenzene and xylene isomers was used for the experimentation. Hence, they were expected to hinder the movement of reactant molecules both on the external surface and within the zeolite channels. It was observed that irrespective of the different feed compositions the concentration of the xylene isomers was intact in the product. There is no other byproducts formation like para-ethylmethyl benzene. The effects of varying the concentration of aromatic compounds in the feed on ethylbenzene conversion and product distribution over the parent and modified H-ZSM-5 catalyst have been discussed. Ethylbenzene disproportionation reaction follows the pseudo first order reaction with an activation energy of 8.6 kcal/mol.
Keywords: Catalyst; diethylbenzene; disproportionation; ethylbenzene; xylene isomers

Dodecatungstophosphoric acid supported on acidic clay catalyst for disproportionation of ethylbenzene in the presence of C-8 aromatics - Bokade, Vijay V.; Yadav, Ganapati D. (Industrial & Engineering Chemistry Research, 2012)
Vapor-phase disproportionation of ethylbenzene (EB) to diethylbenzene (DEB) in a single step is industrially relevant. Diethylbenzene is an important raw material for the conversion of divinylbenzene monomer. Conventionally, it is prepared from diacetophenone by reduction. It is also prepared by vapor-phase alkylation of ethylbenzene with ethylene/ethanol using zeolitic catalysts. In the current work, the efficacy of dodecatungstophosphoric acid (DTPA) supported on acid-treated clay has been evaluated in the disproportionation of ethylbenzene. A 20% (w/w) DTPA/K-10 clay catalyst was found to be efficient and robust. An industrial feed having different compositions of ethylbenzene and xylene isomers was used for the experimentation. Hence, they were expected to hinder the movement of reactant molecules on the catalyst surface. It was observed that irrespective of feed composition the concentration of the xylene isomers was intact in the product. There was no other byproduct formation like p-ethylrnethylbenzene. Optimization of process parameters is presented. The effect of varying the concentration of aromatic compounds in the feed on ethylbenzene conversion and product distribution over the plain clay (K-10) and heteropolyacid-loaded clay catalyst have been discussed. The effect of catalyst bed length to inner diameter of reactor (L/D) ratio on the ethylbenzene conversion and selective formation of p-diethylbenzene (p-DEB) are also discussed.

Direct synthesis of diethyl carbonate from ethanol and carbon dioxide over ceria catalysts - Giram, Ganesh G.; Bokade, Vijay V.; Darbha, Srinivas (New Journal Of Chemistry, 2018)
Direct synthesis of diethyl carbonate (DEC) by carboxylation of ethanol with CO2 was investigated over ceria catalysts. 2-Cyanopyridine (2-CP) was used for trapping water formed in the reaction and to shift the equilibrium towards the product side. An optimal dependence (volcanic plot) of the catalytic activity on the acidity/basicity molar ratio was observed. Neat ceria (procured from Daiichi Kigenso Kagaku Kogyo Co. Ltd, Japan) showed higher catalytic activity than metal incorporated ceria catalysts. CeO2 had the right kind of acidity/basicity ratio to activate ethanol and CO2 simultaneously, yielding DEC. The catalyst was reusable. The yield of DEC obtained in this study using the commercial catalyst was higher than that reported by others using ceria catalysts prepared by other methods. Under optimum conditions (ethanol:2-CP molar ratio = 2:1, catalyst = 2.17 wt% with respect to ethanol, CO2 pressure = 40 bar, reaction temperature = 150 degrees C and reaction time = 3 h) in a batch reaction, a DEC yield as high as 45 mol% (i.e., 38.7 mmol mmol(-1) of CeO2) was obtained.

Direct conversion of N-acetyl-d-glucosamine to N-containing heterocyclic compounds 3-acetamidofuran and 3-acetamido-5-acetyl Furan - Shaikh, Samrin S.; Patil, Chetana R.; Lucas, Nishita; Bokade, Vijay V.; Rode, Chandrashekhar V. (Waste and Biomass Valorization, 2023)
Purpose Effectual waste utilization from plant as well as marine biomass has gained tremendous importance with reference to sustainability. The valorization of marine biomass produces value added compounds containing not only C, H, O but also renewable N atom in the skeleton which widens the scope for its exploration which may prove to be economically beneficial to the society. Heterogeneous catalytic transformation of marine biomass i.e. N-acetyl glucosamine (NAG) to N-substituted aromatic heterocyclic furan derivatives is reported for the very first time. Cost effective and stable metal oxide catalysts were deployed for the transformation. Catalyst screening study showed that La2O3 was found to be an excellent catalyst for N-acetyl glucosamine (NAG) dehydration which mainly produced 3-acetamidofuran (3AF). Methods The physicochemical properties of the metal oxide catalyst were investigated by various techniques such as XRD, FTIR, MeOH-FTIR, TPD, SEM, N-2 sorption studies and HR-TEM analysis for structure activity relationship. Results The effect of various reaction parameters such as catalyst concentration, reaction temperature, reaction time and solvent effect on dehydration of N-acetyl glucosamine has been studied in detail for higher yields. The results revealed that the presence of weak basic sites which are Bronsted in nature and nano pores present on the surface were responsible for improved dehydration of the chitin biomass to selectively yield 3-acetamidofuran (3AF). La2O3 catalyst showed optimum 50% 3AF yield from N-acetyl glucosamine at 180 degrees C in 3 h. Conclusion Efficacious exploitation of marine biomass to value added chemicals using heterogeneous catalysts can be extensively exploited. Separation of N-substituted heterocyclic aromatics is the most innovative aspect of the current study. Thus, utilization of heterogeneous catalyst and renewable biomass as a raw material indicates a transition towards more sustainable and greener approach.{GRAPHICAL ABSTRACT
Keywords: 3-acetamido-5-acetylfuran; 3-acetamidofuran; dehydration; heterogeneous catalysis; Lanthanum oxide; N-acetyl-D-glucosamine; renewable feedstock

Direct conversion of methane to formic acid over Au-Fe-NaZSM-5 at ambient pressure using H2O2 - Kumar, Pawan; Ahangar, Iqra; Kesarwani, Srishti; Urkude, Rajashri; Patil, Nita A. R.; Niphadkar, Prashant; Bokade, Vijay V.; Haider, M. Ali; Vinod, C. P. (Catalysis Science & Technology, 2026)
Direct conversion of methane to value-added products is a long-standing challenge. This report presents the one-step conversion of methane to oxygenates using H2O2 as an oxidant over an Au and Fe supported on NaZSM-5 (0.1Au0.1FeNZ) catalyst, which produces 4264 mu mol of oxygenates with 89% selectivity toward formic acid at 10 bar and 60 degrees C within 30 min in a batch process. The catalyst also produces 26.5 mu mol of oxygenates with 70% selectivity for formic acid at atmospheric pressure and 80 degrees C in a continuous flow process over 9 h of reaction time, making it the first report of such a process. The synergistic interaction of Au and Fe, with the crucial role of Na ions in the zeolite framework in driving the reaction, is revealed through various characterization tools like TEM, XPS, and XAS. Theoretical studies elucidate the active sites responsible for lowering the activation barrier for the crucial C-H activation step. Thus, the catalyst enables the conversion of methane into formic acid with high activity and selectivity, offering new possibilities for harnessing this potent greenhouse gas under process-friendly conditions that were previously unexplored.